Acute megakaryoblastic leukemia with trisomy 3 and CBFA2T3:GLIS2: A case report. Issue 8 (30th March 2022) - Gillam, Joseph; Catic, Aida; Paulraj, Prabakaran; Dalton, Justin; Lai, Guanhua; Jackson‐Cook, Colleen; Turner, Scott; Ferreira‐Gonzalez, Andrea; Barrie, Elizabeth
Abstract: Non‐Down‐syndrome‐related acute megakaryoblastic leukemia (non‐DS‐AMKL) is a rare form of leukemia that can present with a variety of initial symptoms, including fever, rash, bruising, bleeding, or other more clinically challenging symptoms. Herein, we describe a 19‐month‐old female patient who presented with left lower extremity pain and language regression who was diagnosed with AMKL, not otherwise specified (NOS), on the basis of peripheral blood and bone marrow analysis, as well as cytogenetic and molecular diagnostic phenotyping. Of note, in addition to this patient's karyotype showing trisomy 3, a fusion between CBFA2T3 (core‐binding factor, alpha subunit 2, translocated to, 3) on chromosome 16 and GLIS2 (GLIS family zinc finger protein 2), also on chromosome 16, was observed. Patients with AMKL who have trisomy 3 with CBFA2T3::GLIS2 fusions are rare, and it is not known if the co‐occurrence of these abnormalities is coincidental or biologically related. This highlights the continued need for further expansion of genetic testing in individuals with rare disease to establish the groundwork for identifying additional commonalities that could potentially be used to identify therapeutic targets or improve prognostication.